Pengaruh Perilaku Organisasi Terhadap Prestasi Karyawan pada PT. Niagatama Intimulia Makassar - Nur Soleh Kamalludin; Suwandi (Teewan Journal Solutions, 2025)
This study aims to examine the effect of organizational behavior on employee performance. Organizational behavior consists of two variables, namely individual behavior and group behavior. Respondents in this study were 170 employees of PT. Niagatama Intimulia Makassar, using t-test and f-test analysis with the help of SPSS 12. This study found that individual behavior and group behavior had a positive and significant effect on employee performance. From the two independent variables it can be seen that the group behavior variable is more dominant in influencing employee work performance, this is because with the cohesiveness in working in a team or group, they can deal with various problems that arise at work.